2003
DOI: 10.1002/jnr.10669
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐independent cell death by low concentrations of nitric oxide in PC12 cells: Involvement of cytochrome C oxidase inhibition and the production of reactive oxygen species in mitochondria

Abstract: We reported previously that low levels of nitric oxide (NO) induced cell death with properties of apoptosis, including chromatin fragmentation and condensation in undifferentiated PC12 pheochromocytoma cells. The present study demonstrates that cytotoxicity of low concentrations of NO is mediated by inhibition of mitochondrial cytochrome c oxidase and generation of reactive oxygen species (ROS). An NO donor, (+/-)-(E)-4-ethyl-2-[(E)-hydroxyimino]-5-nitro-3-hexenamide (NOR3) induced cell death even at low conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…The exact mechanism of the anti-apoptotic effect of CORM-A1 in MODE-K cells remains to be clarified, but our study shows that its anti-apoptotic effect correlates with a reduction in ROS production, which was more pronounced than that 19 observed with bilirubin, as well as an increase in GSH levels. Indeed, caspase-independent induction of apoptosis by ROS has been reported in PC12 pheochromocytoma cells so that inhibition of ROS production per se can be expected to reduce apoptosis [50]. The finding that CORM-A1 exerts significant protection against both TNF-α/CHX-induced oxidative stress and apoptosis supports the notion that CO can mediate the well-known anti-apoptotic effect of HO-1.…”
Section: Influence Of Ho-1 Related Products On Tnf-α/chx-induced Oxidsupporting
confidence: 56%
“…The exact mechanism of the anti-apoptotic effect of CORM-A1 in MODE-K cells remains to be clarified, but our study shows that its anti-apoptotic effect correlates with a reduction in ROS production, which was more pronounced than that 19 observed with bilirubin, as well as an increase in GSH levels. Indeed, caspase-independent induction of apoptosis by ROS has been reported in PC12 pheochromocytoma cells so that inhibition of ROS production per se can be expected to reduce apoptosis [50]. The finding that CORM-A1 exerts significant protection against both TNF-α/CHX-induced oxidative stress and apoptosis supports the notion that CO can mediate the well-known anti-apoptotic effect of HO-1.…”
Section: Influence Of Ho-1 Related Products On Tnf-α/chx-induced Oxidsupporting
confidence: 56%
“…Furthermore, the Aβ-induced apoptotic cell death in PC12 cells is associated with the decreased expression of the anti-apoptotic molecule Bcl-2 and the increased expression of the pro-apoptotic molecule Bax (Xiao et al, 2002;Yuyama et al, 2003). The activation of caspase-3 plays a role in Aβ-induced apoptosis (Allen et al, 2001) and an increase in activated caspase-3 has been reported in AD brains (Su et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…concentration of oxygen, superoxide radical and thiols), may induce cell death via programmed mechanisms or by necrosis, is extensively documented (Borutaite and Brown, 2005) in several cell types (Bal-Price and Brown, 2000;Terwel et al, 2000;Yuyama et al, 2003). These reports differ not only in the cell type studied but also in the steady-state concentration of the NO, redox species involved and the chemistry it undergoes in a given biological milieu.…”
Section: Discussionmentioning
confidence: 99%